2016
DOI: 10.1016/j.jacr.2015.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Lecture Evaluations by Medical Students: Concepts That Correlate With Scores

Abstract: Purpose: The didactic lecture remains one of the most popular teaching formats in medical education; yet, factors that most influence lecturing success in radiology education are unknown. The purpose of this study is to identify patterns of narrative student feedback that are associated with relatively higher and lower evaluation scores.Methods: All student evaluations from our core radiology elective during 1 year were compiled. All evaluation comments were tagged, to identify discrete descriptive concepts. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 21 publications
1
12
0
3
Order By: Relevance
“…Praise was also given to lectures with some form of audience response system as this was felt by the students to enhance engagement with the speaker and the material. These results are similar to results from a recent study that reported on patterns of narrative student feedback that are associated with relatively higher and lower evaluation scores (12). The Zoom chat function was also well received and created an ongoing dialogue during the lectures to enhance student engagement and understanding.…”
Section: Discussionsupporting
confidence: 87%
“…Praise was also given to lectures with some form of audience response system as this was felt by the students to enhance engagement with the speaker and the material. These results are similar to results from a recent study that reported on patterns of narrative student feedback that are associated with relatively higher and lower evaluation scores (12). The Zoom chat function was also well received and created an ongoing dialogue during the lectures to enhance student engagement and understanding.…”
Section: Discussionsupporting
confidence: 87%
“…This is possibly because trainees had a better understanding of what was expected of a senior medical student or that they spent more time with students. Previously, residents have been identified as comparable lecturers to faculty members but this is the first study to document their role in clinical electives [16]. Across specialties, there is a movement to formalize programs related to residents as teachers in order to develop residents’ teaching skills in an evidence-based manner [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…The feedback questionnaire or statements should be elaborated in cooperation with the students and the lecturers, to find the interesting focus for both sides. Other possibilities could be discussed like emotional adjectives instead of statements (Belch and Law, 2018) or targeting on factors which are motivating for students to follow the lecture like interactiveness, fun/engaging, or practical importance (Jen et al, 2016). This underlines the statements of Malik and Malik, that it is of great importance to integrate the students in the evaluation processes (Malik and Malik, 2012).…”
Section: Discussionmentioning
confidence: 99%